Study on Car Speed Characteristics at 60km/hr Speed Limit Zone on Federal Route FT050 - OMAR, ROSHASNIZA; OMAR, NOORLIYANA (Recent Trends in Civil Engineering and Built Environment, 2021)
Johor is one of the states in Malaysia that recorded high accident statistics, especially Federal Route FT050, Batu Pahat-Ayer Hitam. On average, this road has recorded more than 1000 accidents and 36 deaths every year since 2006 involving all types of vehicles and identified as a "dead road" by the Ministry of Works Malaysia. The attidude of driver who refused to comply the speed limit and drive in high speed is the main factor contribute to accident while making car as a safe transport to the contrary. The study conducted to determine driver speed limit compliance through car driver speed analysis. The GPS DG 200 was used to record the speed data of 50 trips at Batu Pahat to Ayer Hitam (Direction 1) and 42 trips at Ayer Hitam to Batu Pahat (Direction 2). The data were analyzed using 2-Sample T-Test to compare the car speed data from both directions at Sekolah Kebangsaan Bukit Soga and Ayer Hitam Fire Station to determine the level of compliance of car drivers with the speed limit of 60km/h. The result shows, driver from Direction 1 use higher speed, with speed range of 60 km/h - 100 km/h compared to Direction 2 which is 20 km/h - 90 km/h. Based on these findings, 97% drivers comply the speed limit and 3% drivers violated speed limits at Ayer Hitam Fire Station meanwhile 79% complied while the other 21% violated speed limits at Sekolah Kebangsaan Bukit Soga. The overall findings found that the level of compliance with the driver speed limit is still at a weak level where the choice of driver speed is maybe influenced by environmental conditions and road geometry.